Sit-stand desks in call centres: Associations of use and ergonomics awareness with sedentary behavior - Straker, Leon; Abbott, R.; Heiden, M.; Mathiassen, S.; Toomingas, A. (Elsevier, 2013)
Objective: To investigate whether or not use of sit–stand desks and awareness of the importance of postural variation and breaks are associated with the pattern of sedentary behavior in office workers.Method: The data came from a cross-sectional observation study of Swedish call centre workers. Inclinometers recorded ‘seated’ or ‘standing/walking’ episodes of 131 operators over a full work shift. Differences in sedentary behavior based on desk type and awareness of the importance of posture variation and breaks were assessed by non-parametric analyses.Results: 90 (68.7%) operators worked at a sit–stand desk. Working at a sit–stand desk, as opposed to a sit desk, was associated with less time seated (78.5 vs 83.8%, p = 0.010), and less time taken to accumulate 5 min of standing/walking (36.2 vs 46.3 min, p = 0.022), but no significant difference to sitting episode length or the number of switches between sitting and standing/walking per hour. Ergonomics awareness was not associated with any sedentary pattern variable among those using a sit–stand desk.Conclusion: Use of sit–stand desks was associated with better sedentary behavior in call centre workers, however ergonomics awareness did not enhance the effect.